Referendum design, quorum rules and turnout - Conraria, Luís Aguiar (2008)
What is the impact of different referenda designs on the willingness of the electorate to vote? In this article, we focus on quorum requirements. We use a rational choice-voting model to demonstrate that certain types of quorum requirements change the incentives each elector faces. In particular, participation quorums induce electors who oppose changes in the status quo and expect to be in the minority to abstain rather than vote. As a result, such quorums decrease turnout. We test this model prediction using data for all referendums held in current European Union countries from 1970 until 2007. We show that that the existence of participation quorums does increase abstention by 10 percentage points.